An Overview of Urdu Mahia - Dr. Zeenat Bibi; Dr Muhammad Nasir Afridi; Dr. Sajid Javed (Zaban-o-Adab, 2023)
Franz Kafka is what only Franz Kafka could be. He was one of the stalwarts of twentieth century literature who hued out new vistas of meanings in literature, carved a niche in literary genre called ' Kafkaesque ' and leaving questions through his creative works that have the ability to continue to haunt his discerning readers. Translated into urdu, Kafka has come to create a special bond with his urdu language readers through some splendid translations which have removed semantic barriers between the creator and his avid audience. In the present article, the writer has focused on Kafka's two seminal works; Metamorphisis and The Trial to bring out issues which permeate Kafka's writing. Different layers of meaning and literary interpretations of these two works have been analyzed threadbare so as to understand Kafka through the prism of multiple perspectives.